Circ_0067934 reduces JNK phosphorylation through a microRNA-545-3p/PPA1 axis to enhance tumorigenesis and cisplatin resistance in ovarian cancer. (4th March 2022) - Yin, Yingchun; Li, Jing; Rong, Jiansheng; Zhang, Baohua; Wang, Xinmei; Han, Hongmei
Abstract: Background: Circular RNA 0067934 (circ_0067934) has been revealed as a cancer driver in multiple human malignancies, whereas its action in the pathogenesis of ovarian cancer (OC) remains unclear. This study focuses on the function of circ_0067934 in tumorigenesis and cisplatin (DDP) resistance in OC and the molecular mechanism. Methods: Expression of circ_0067934 in OC tissues and cells was examined, and its correlation with the clinical characteristics of patients was analyzed. Candidate targets of circ_0067934 were predicted using bioinformatics systems. Binding relationships between circ_0067934 and microRNA (miR)-545-3p and between miR-545-3p and inorganic pyrophosphatase 1 (PPA1) were validated via luciferase assays. Gain- and loss-of functions of circ_0067934, miR-545-3p and PPA1 were performed to determine their functions in proliferation, invasion, apoptosis and DDP resistance of OC cells in vitro and in vivo . Results: Circ_0067934 was overexpressed in OC samples and associated with advanced tumor staging and lymph node metastasis. Downregulation of circ_0067934 reduced DDP resistance of the DDP-resistant A2780/DDP cell line and reduced cell proliferation and invasion, but the malignant behaviors of OC cells were restored after further miR-545-3p downregulation. Circ_0067934 served as a sponge for miR-545-3p and diminished its suppressive effect on PPA1 translation. Artificial upregulation of PPA1 enhanced proliferation, invasion and DDP resistance of A2780/DDP cells, and it reduced phosphorylation of the pro-apoptotic JNK signaling. Similar results were found in vivo . Conclusion: This study suggests that circ_0067934 sequesters miR-545-3p and enhances PPA1 expression to promote tumorigenesis and DDP resistance in OC. This study may provide novel approaches in the management of OC.